The Effect of Laban Leaf Ethanol Extract Cream (Vitex pinnata) on Wound Healing on Male White Rats (Rattus norvegicus) Wistar Strain - Simorangkir, Delisma Marsauli; Evi Depiana; Masria Sianipar; Chindy Umaya; Gratia Apulina (Jurnal FARMASIMED (JFM), 2025)
Wound healing is a process that involves the restoration of injured or dead tissue and replacing it with new tissue through the process of cell regeneration. Although the wounds that occur tend to be mild, they need to be treated immediately to avoid infection that will hinder the healing process, even causing dangerous diseases. Therefore, natural product-based treatments have been explored naturally because of their ability to provide optimal wound healing effects to patients such as laban leaves (Vitex pinnata). The method used in this study was a laboratory experiment that began with the manufacture of extracts, cream formulations, and testing of wound healing activity. The test animals, male white rats of the Wistar strain, were divided into 5 groups for different treatments. Wound healing activity was measured by observing the diameter of the wound and healing time, and analyzed statistically using the One Way Anova method. The results showed that the preparation of ethanol extract cream of laban leaves (Vitex pinnata) was effective in accelerating the healing of cuts in male white rats at a concentration of 25% which was almost the same as the positive control. The conclusion of this study shows that the ethanol extract of laban leaves (Vitex pinnata) can be formulated into an effective cream preparation for wound healing, with a concentration of 25% as the most optimal concentration.